Potential Therapeutic Effects of Tali Bamboo Leaf Tea (Gigantochloa apus) on Lipid Profile of Rats With Metabolic Syndrome - Mujayanah, Ani Rosa Putri Ayu; Sari, Yulia; Listyawati, Shanti (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to determine the potential of Tali bamboo leaf tea (Gigantochloa apus) on the lipid profile of metabolic syndrome rats. This study is an laboratory-based experimental study using 30 male Wistar rats with metabolic syndrom aged 8 weeks and weighed 150–250 g, that were divided into 5 groups namely negative control (K-), positive control (K+), and three intervention groups with intervention doses of bamboo leaf tea at 300, 600, and 900 mg/200 g BW for 28 days. The results showed that there were significant differences (p<0.05) in High- Density Lipoprotein Cholesterol (HDL-C) and Low-Density Lipoprotein Cholesterol (LDL-C) levels before and after intervention. Tali bamboo leaf tea has the potential to improve the lipid profile of rats with metabolic syndrome (p<0.001).